Beyond social media users and game players: patterns of digital media use and their association with personality traits - Stojković, Irena; Mentus, Tatjana; Jelić, Marija; Filipović, Božidar; Veselinović, Marijana (Frontiers in Psychology, 2026)
IntroductionFollowing the uses and gratifications theoretical framework, the objectives of the present study were to employ a person-centered approach to identify patterns of digital media use based on motivations, activities, and content, and to examine the role of personality traits in differentiating these profiles.MethodsThe samples of high school and university students from Belgrade, Serbia, participated in Study 1, a qualitative focus group study aimed to investigate aspects of digital media use through qualitative content analysis; and Study 2, a quantitative study of constructing digital media use scales, establishing patterns of digital media use through latent profile analysis, and investigating their associations with personality traits.ResultsThe created scales of digital media use demonstrated adequate construct validity, reliability, and measurement invariance across gender. Seven distinct profiles of digital media use were identified. The profiles High Social Media Users, Social Media Lurkers, Video Game Players, and Low Digital Media Users align with previous research. Three novel profiles were established: Science-Oriented Users, Creative Users, and Aggression-Oriented Users. Discriminant analysis revealed that personality traits significantly predicted profile membership. A combination of high Openness and Extraversion primarily distinguished Creative Users from Aggression-Oriented Users, Video Game Players, and Low Digital Media Users. High Neuroticism combined with low Conscientiousness best differentiated Aggression-Oriented Users from Science-Oriented Users. Finally, a function primarily defined by low Agreeableness predicted membership in the Aggression-Oriented Users profile versus the Social Media Lurkers profile.DiscussionThe findings offer implications for designing interventions that promote beneficial media use among young people.